REINFORCEMENT POSISITIF DALAM PEMBELAJARAN BAHASA ARAB DI MADRASAH TSANAWIYAH NEGERI KOTA PEKANBARU RIAU - ZALYANA, ZALYANA (Potensia, 2014)
This research is motivated by the importance of giving positive reinforcement in the learning of the Arabic language to students in the learning process in the classroom. This is due to the low motivation of students in learning of the Arabic language, therefore teachers have need to provide motivation in the form of reinforcement whether verbal or non-verbal. This research was conducted to know the form of positive reinforcement of what has been conducted by teachers of Arabic language at State Islamic Junior High School in the learning process in the classroom. To answer the question above the authors conducted interviews with the six teachers of Arabic language in three State Islamic Junior High School Pekanbaru. After the data is collected and analyzed by qualitative descriptive method with the percentage was found the results that teachers of Arabic language using varied reinforcement meaning that sometimes they are using verbal forms such as word ahsanta, jayyid, jayyid jiddan,; and sometimes in the form of non-verbal, such as; giving the smile, applause, and thumbs up. It turns out that giving these reinforcement have an effect to activity of students in learning Arabic